Élmények és tárgyak fogyasztásának kapcsolata a szubjektív jólléttel - Tamás Hajdu; Gábor Hajdu (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
– In this paper we analyze whether people who spend money on experiences rather than material things are more satisfied. Previous psychological studies have several drawbacks, and therefore their results might be biased and unreliable. Trying to avoid these drawbacks in this research we use large-scale representative survey databases from Hungary. In the first study we analyze two pooled cross-sectional surveys (TÁRKI Household Monitor 2005 and 2007), in the second study we analyze a subsample of the Hungarian Household Budget Survey (HBS). We estimate the association of expenditures with life satisfaction using linear and non-linear models as well. We demonstrate that experiences associate stronger with life satisfaction than material things, thus our evidences based on survey data corroborate the previous results from the psychological experiments. In addition, we show that marginal effect of material expenditures is diminishing, whereas marginal effect of experiential expenditures is constant. It means that, ceteris paribus, a reallocation of the expenditures might increase individuals' well-being. The magnitude of this gain is similar to a 10 percent increase in income and expenditures. Although this analysis is not able to establish causality between expenditures and satisfaction, at the end of the paper we suggest a minor modification of the HBS which can make possible to analyze the causal relationship between expenditures and well-being.
Keywords: I31; D12; 330; subjective well-being; satisfaction; expenditures; consumption